Pisang Gen Alfa: A Smartphone Application To Reduce Parenting Stress For Parents With Alpha Generations - Ahmad Guntur Alfianto; Nicky Danur Jayanti (Universitas Muhammadiyah Semarang, 2020)
Parenting stress experienced by parents for alpha generation. Efforts that can be done are to reduce parenting stress with the right techniques. One technique to reduce stress is PISANG GEN ALFA/Mobile Application Parenting Assertive and Management Stress. The purpose of this study was to analyse the effect of PISANG GEN ALFA on parenting stress for parents with alpha generation. The method used was a quasi-experimental pre-test-post-test with control group design with a sample of 100 parents with alpha generation. The sampling technique was purposive sampling with research instruments using the Parental Stress Scale (PSS). The research was conducted in Malang City and Batu City. The statistical test used Chi-Square Tes, Paired Sample T-Test and independent T-test. The results of the distribution of characteristics were not different between the two groups before and after being given treatment. There was an effect of reducing parenting stress after being given PISANG GEN ALFA (0,000) and there was an average difference between the treatment and control groups (0.001). PISANG GEN ALFA is one of the mental health applications that can reduce parenting stress in parents with alpha generation. So that there was a reduction in parenting stress after being given PISANG GEN ALFA and there was an average difference between the group using PISANG GEN ALFA compared to the control group in reducing parenting stress for parents with generations of the children.